Kinetic parameters determination of FCC gasoline hydrotreating using genetic algorithms - Giraldo Duarte, Sonia A.; Pérez Martínez, David de Jesús; Bravo Villarreal, Carlos Eduardo; Granados Zarta, Gustavo Alberto; Celis Cornejo, Carlos Mauricio (CT&F - Ciencia, Tecnología y Futuro, 2013)
The kinetics parameters for the simultaneous reactions of hydrodesulfurization and hydrogenation of synthetic Fluid Catalytic Cracking (FCC) naphtha over CoMo/y-Al2O3 catalyst were determined. The proposed kinetic model considered a Langmuir-Hinshelwood adsorption mechanism (with 16 steps) with just one kind of active site. The amount of experimental data obtained was relatively limited, thus a genetic algorithm accompanied by an optimization through the Nelder-Mead Simplex method were used for the parameter estimations. Trimethylpentenes and 2-methylthiophene were used as representative molecules of unsaturated and sulfur compounds in FCC naphtha respectively. It was possible to calculate kinetic and thermochemical parameters, such as activation energies, adsorption heats and frequency factors with a good enough approach. This methodology results very useful since it allows the parameters determination with accuracy, reducing the amount of experimentation in comparison with traditional methodologies.